2022
DOI: 10.3390/ijerph19031094
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study Evaluating the Influence of Front-of-Package Warning Labels on Adolescent’s Purchase Intention of Processed Food Products

Abstract: Front-of-package warning labels (WLs) are among the public health policies adopted by some countries, mainly in Latin-America, to tackle childhood obesity; however, their impact is still under review. The aim of this study was to assess, using an experimental design, whether WLs influence purchase intention of processed foods and identification of the healthiest products among adolescents in Peru, in May 2019, just before WLs mandatory implementation. Four hundred forty-nine adolescents from two public schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…When considering studies published from mid-2018, 47 new set of data were identified and analyzed [ 12 , 20 , 23 , 24 , 27 , 29 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 46 , 49 , 50 , 51 , 52 , 53 , 55 , 56 , 58 , 59 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 78 , 79 , 81 ]. Among those, 23 compared two of the four FOPNL of interest or more.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering studies published from mid-2018, 47 new set of data were identified and analyzed [ 12 , 20 , 23 , 24 , 27 , 29 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 46 , 49 , 50 , 51 , 52 , 53 , 55 , 56 , 58 , 59 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 78 , 79 , 81 ]. Among those, 23 compared two of the four FOPNL of interest or more.…”
Section: Resultsmentioning
confidence: 99%
“…Among those, 23 compared two of the four FOPNL of interest or more. Most studies found a favorable impact of at least one FOPNL on at least one measure and only five studies (11%) did not find any effect on selection/purchasing behavior [ 12 , 38 , 39 , 52 , 63 , 71 ]. Conversely, several comparative studies reported a lack of effect of at least one FOPNL, even though another one was found effective.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the proposed NIP plus an octagonal FoP label (iii) had the lowest proportion of participants choosing high-in-sugar products for whole-grain biscuits, yoghourts, and across all products. Studies conducted in neighbouring Latin American countries have demonstrated that FoP octagonal warning labels effectively reduce consumer choice of foods high in critical nutrients ( 47 , 49 , 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, experimental studies have shown that this type of FOPL has a more accurate effect on reducing the purchase of foods high in certain nutrients, such as sugar (Alcantara et al., 2020; Ang et al., 2019; Jáuregui et al., 2020), total calories, saturated fat, total fat, and sodium (Jáuregui et al., 2020). On the other hand, a study of Peruvian adolescents conducted shortly before the introduction of WL in Peru found no differences between the group without FOPL and the group with FOPL in terms of purchase intentions and identification of the option with the lowest levels of added sugars, saturated fat, and sodium (Saavedra‐Garcia et al., 2022). The authors argue that WL may not be sufficient to influence the purchase intentions of adolescents from low‐ to moderate‐income communities, but this hypothesis was not tested in the study.…”
Section: Fopl Effects On Consumer Behaviormentioning
confidence: 99%
“…All FOPL models were found to have some barriers to their effectiveness on consumer behavior. It seems that taste, aroma, brand, and price are considered more important than the message conveyed by FOPL (Freire et al., 2017; Pettigrew et al., 2016; Saavedra‐Garcia et al., 2022). For example, an experimental study demonstrated that when there was one or two WLs, purchase intentions for products, such as granola bars and margarine, decreased, while this effect was not evident in the case of ice cream and ketchup (Uribe et al., 2020).…”
Section: Fopl Effects On Consumer Behaviormentioning
confidence: 99%